The economic valuation of cultural events in developing countries: combining market and non-market valuation techniques at the South African National Arts Festival - Snowball, Jeanette Dalziel (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2006)
The arts in many countries, but particularly in developing ones, are coming under increasing financial pressure and finding it difficult to justify the increases in government funding needed to maintain and grow the cultural sector. The trend in cultural economics, as well as in other areas, appears to be towards including qualitative valuations, as well as the more traditional quantitative ones. This thesis argues that the value of cultural events should include long term historical qualitative analysis, financial or economic impact and a valuation of the positive externalities provided by cultural events and that any one of these should only be regarded as a partial analysis. Four methods of valuing the arts using the South African National Arts Festival (NAF) as an example are demonstrated. Firstly, a qualitative historical analysis of the role of the NAF in South Africa's transformation process from Apartheid to the democratic New South Africa is examined, using theories of cultural capital as a theoretical basis. It is argued that the value of cultural events needs to take into account long-term influences especially in countries undergoing political and social transformation. The second valuation method applied is the traditional economic impact study. Four economic impact studies conducted on the NAF are discussed and methodologies compared. It is concluded that, despite the skepticism of many cultural economists, the method can provide a useful partial valuation and may also be used for effective lobbying for government support of the arts. Chapter four discusses willingness to pay studies conducted at the NAF in 2000 and 2003 (as well as a pilot study conducted at the Klein Karoo Nationale Kunstefees). It is found that lower income and education groups do benefit from the positive externalities provided by the Festival and that this is reflected in their willingness to pay to support it. It is also argued that such contingent valuation studies can provide a reasonably reliable valuation of Festival externalities, but that they may be partly capturing current or future expected financial gains as well. Finally, the relatively new choice experiment methodology (also called conjoint analysis) is demonstrated on visitors to the NAF. The great advantage of this method in valuing cultural events is that it provides part-worths of various Festival attributes for different demographic groups. This enables organizes to structure the programme in such a way as to attract previously excluded groups and to conduct a cost-benefit analysis for each part of the Festival.
Keywords: Standard Bank National Arts Festival -- Economic aspects; Performing arts festivals -- Economic aspects -- South Africa -- Grahamstown; Arts -- South Africa -- Economic aspects; Finance -- South Africa; Arts -- South Africa -- Finance; Arts -- South Africa -- Political aspects; Finance, Public -- South Africa; South Africa -- Politics and government -- 1994-